The Energy Biosciences Institute : a novel partnership or a sellout? - Chesbrough, Henry William, (SAGE Knowledge. Cases., 2017)
The EBI case study is an open innovation case study. It documents a proposed partnership between the University of California-Berkeley and BP (formerly British Petroleum). The case study addresses issues from both sides. In the event Berkeley and BP agree to create the Energy Biosciences Institute together, this will lead to a $500 million partnership between British Petroleum, Berkeleys Lawrence Berkeley National Laboratory, and the University of Illinois at Urbana-Champaign. The case study features protagonist, Beth Burnside, who was the Vice Chancellor for Research at Berkeley during the time of the negotiations.